Analisis Pilihan Kata Teks Deskripsi Kelas IV di UPT SD Negeri 04 Petrokimia Gresik - Hasanah, Anis Faridotul; Huda, Syaiful; Marzuki, Ismail (JURNAL ILMIAH NUSANTARA, 2025)
The purpose of this research is to analyze and evaluate descriptive text objects that are heard and read orally, written and visually. Find standard word choices from descriptive texts written by students and analyze word choice errors and their effect on sentence clarity. This research uses a qualitative method which is carried out through several stages, namely, data collection which is carried out using the observation method. Data analysis was collected using marking techniques by reading and then marking. The results of this research show that descriptive text is writing that aims to present details about an object in such a way that it can influence the sensitivity and imagination of the reader or listener as if they could see, hear and feel the object directly. Word choice or diction is very important when writing descriptive text. Good choice of words makes the text beautiful and interesting. Apart from that, word choice also affects the clarity of sentences. The choice of words when writing descriptive text is very necessary so that the writing reaches the reader correctly